Advancements in Transdermal Drug Delivery Systems (TDDS): A Comprehensive Review of Skin as a Viable Route for Systemic Drug Administration (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
TDDS, commonly known as transdermal patches, represent a significant advancement in pharmacological treatments, allowing drugs to be delivered through the skin directly into the systemic circulation. This method offers consistent plasma drug levels, enhanced patient compliance and avoidance of hepatic first-pass metabolism. The application of substances to the skin for therapeutic purposes has historical roots, but it was only in the mid-20th century that the skin was explored as a viable route for systemic drug administration. This review discusses the evolution and current state of TDDS, highlighting the various technologies employed to enhance drug permeation, such as the use of microneedles and novel polymeric materials. It also evaluates the role of penetration enhancers like dimethyl sulfoxide (DMSO) in improving the delivery efficiency of active compounds. Despite the challenges, such as the limited range of suitable drugs and the need for optimal skin adhesion, the ongoing innovations in TDDS design promise to expand their use in managing chronic diseases and improving overall patient care. The review synthesizes recent research, providing a comprehensive overview of the progress and potential of TDDS in modern healthcare.